Analysis of the Feasibility of the Nentu Raw Material Handicraft Business (Paku Hata) (Case Study of the Nentu Daharia Business, Lakarinta Village, Lohia District, Muna Regency) - Wa Ode Febryosan; Ine Fausayana; Abdi (International Journal of Technology and Education Research, 2026)
This study aims to determine the amount of profit and the feasibility of a handicraft business made from nentu raw materials from a financial perspective. The research was conducted at Wa Daharia’s nentu handicraft business located in Lakarinta Village, Lohia District, Muna Regency, from January 2025 until the completion of the study. This research employed a field research approach with a descriptive quantitative method, in which the researcher directly observed the object under study. The research variables included respondent characteristics, namely age, level of formal education, number of family dependents, and secondary employment. The data analysis covered the calculation of production costs, including raw material costs, labor costs, overhead costs, operational costs, and taxes. Furthermore, business feasibility was analyzed using the Revenue Cost Ratio (R/C Ratio), Benefit Cost Ratio (B/C Ratio), Return on Investment (ROI), and Break Even Point (BEP) methods. The results showed that Wa Daharia’s nentu handicraft business generated a profit of IDR 25,181,000 and was financially feasible to operate. The R/C Ratio value was 2.37, the B/C Ratio was 1.38, and the ROI was 138.8%. The BEP price and production values for each product were as follows: large bosara with a BEP price of IDR 268,887.09 and a BEP production level of 9 units; small bosara with a BEP price of IDR 91,261.36 and a BEP production level of 27 units; glass baskets with a BEP price of IDR 91,261.36 and a BEP production level of 27 units; and flower vases with a BEP price of IDR 38,861.70 and a BEP production level of 37 units.